Mobile App for Dental Patient Feedback and Satisfaction Surveys: An Agile Development Perspective - Sihombing, Denny Jean Cross (Jurnal Ekonomi, 2024)
This research examines the development of a dental patient feedback application using the Agile Development approach, focusing on collecting and analyzing patient feedback to enhance the quality of dental healthcare services. The research problem investigates the challenges in effectively collecting and analyzing patient feedback and the need for responsive and adaptive solutions. The research methodology includes user needs analysis, Agile-based application development, user acceptance evaluation through beta testing, and user feedback data analysis. The research findings indicate that using Agile Development can produce an application that effectively supports the collection of patient feedback and receives positive user acceptance. This research contributes to developing an application that can enhance the quality of dental healthcare services through responsive integration of patient feedback and the use of an adaptive and flexible development approach.